GE_GERICHTE C/24925/2012 vom 14. März 2014 - GE Cour de justice (2014)
DIVORCE; CURATELLE ÉDUCATIVE; OBLIGATION D'ENTRETIEN; RÉGIME MATRIMONIAL; PARTICIPATION AUX ACQUÊTS; DÉFAUT(CONTUMACE) | CC.276.1; CC.276.2; CC.285